2018
DOI: 10.3390/mi9110549
|View full text |Cite
|
Sign up to set email alerts
|

Micromixing Study of a Clustered Countercurrent-Flow Micro-Channel Reactor and Its Application in the Precipitation of Ultrafine Manganese Dioxide

Abstract: A clustered countercurrent-flow micro-channel reactor (C-CFMCR) has been assembled by the numbering-up of its single counterpart (S-CFMCR). Its micromixing performance was then studied experimentally using a competitive parallel reaction system, and the micromixing time was calculated as the micromixing performance index. It was found that the micromixing time of C-CFMCR was ranged from 0.34 to 10 ms according to its numbering-up times and the operating conditions of the reactor, and it was close to that of S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…1b-d) was integrated by its counterpart S-CFMCR ( Fig. 1a) as stated in our previous work, 38 which possesses the advantages of easy to fabricate, exible operation and variable magnication factors.…”
Section: Construction Of C-cfmcrmentioning
confidence: 99%
See 1 more Smart Citation
“…1b-d) was integrated by its counterpart S-CFMCR ( Fig. 1a) as stated in our previous work, 38 which possesses the advantages of easy to fabricate, exible operation and variable magnication factors.…”
Section: Construction Of C-cfmcrmentioning
confidence: 99%
“…For this purpose, we built a clustered countercurrent-ow micro-channel reactor (C-CFMCR) by numbering-up its single counterpart, i.e., a single countercurrent-ow micro-channel reactor (S-CFMCR), and studied its micromixing performance (expressed as micromixing time, t m ) experimentally. 38 It was found that C-CFMCR had notable advantages of strengthening micromixing, easy to be fabricated, exible operation in continuous manner and easy to be scaled up with controllable magni-cation times. Hence it was expected to be an efficient technology for the massive precipitation of nanoparticles or ultrane particles.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al presented a multidimensional scale-up strategy for modularized microfluidic reactors to achieve industrial production of functional materials . Cheng et al, in our laboratory, assembled a clustered counter-current-flow microchannel reactor (C-CFMCR) by numbering-up the single counter-current-flow microchannel reactors (S-CFMCR), and it showed that only a very slight amplification effect of S-CFMCR to C-CFMCR on its application in precipitation of MnO 2 was noticed . Although the numbering-up of microchannel reactors has been widely applied, it can only be applied in a limited flow range, beyond which uneven flow distribution will degrade their micromixing performance.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Additionally, Cheng et al assembled a clustered countercurrent-flow microchannel reactor by numbering up single-channel reactors. 30 Despite being most widely used, devices based on numbering-up have a relatively narrow operation flow rate range, and beyond which, the flow maldistribution could deteriorate the mixing performance. The numbering-up structure also complicates device machining.…”
Section: Introductionmentioning
confidence: 99%
“…Such an arrangement can be operated in series to achieve numbering up in a large throughput. With this strategy, Asano et al realized the numbering-up of a microjet mixer, and Su et al achieved the numbering-up of microreactors in applications of free radical polymerization and photoredox catalysis. Constructal distributors with bifurcation configurations serve as alternative numbering-up methods. , Additionally, Cheng et al assembled a clustered countercurrent-flow microchannel reactor by numbering up single-channel reactors . Despite being most widely used, devices based on numbering-up have a relatively narrow operation flow rate range, and beyond which, the flow maldistribution could deteriorate the mixing performance.…”
Section: Introductionmentioning
confidence: 99%